2003
DOI: 10.1097/00008483-200305000-00003
|View full text |Cite
|
Sign up to set email alerts
|

Stepped Care Approach to Smoking Cessation in Patients Hospitalized for Coronary Artery Disease

Abstract: A stepped-care approach to smoking cessation increased short-but not long-term point-prevalent abstinence in patients with CAD. For improvement of long-term effectiveness, refinement of the timing and content of stepped-care interventions needs to occur.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
57
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(57 citation statements)
references
References 26 publications
0
57
0
Order By: Relevance
“…Patients in this group received the minimal intervention plus 45-60 minutes of bedside education and counselling, takehome materials (video, workbook, audiotape) and 7 telephone counselling sessions initiated by the research nurse (2,7,14,21,30,45 and 60 days after discharge). Education covered the patient's personalized risks associated with smoking and the benefits of quitting, as well as withdrawal, weight gain and the benefits of making the home smoke-free.…”
Section: Intensive Interventionmentioning
confidence: 99%
See 1 more Smart Citation
“…Patients in this group received the minimal intervention plus 45-60 minutes of bedside education and counselling, takehome materials (video, workbook, audiotape) and 7 telephone counselling sessions initiated by the research nurse (2,7,14,21,30,45 and 60 days after discharge). Education covered the patient's personalized risks associated with smoking and the benefits of quitting, as well as withdrawal, weight gain and the benefits of making the home smoke-free.…”
Section: Intensive Interventionmentioning
confidence: 99%
“…8 Our results suggest that intensive counselling provided during the hospital stay is more effective than a stepped-care approach that provides intensive counselling only after a patient has relapsed. 30 By significantly increasing abstinence among cardiac patients, inpatient programs for smoking cessation have the potential to produce sizeable reductions in cardiac events 1,3,4,6,7 and hospital costs. [31][32][33][34] In our study, slightly less than half of the identified smokers did not want to quit smoking or refused to participate.…”
Section: Intensive Intervention Minimal Interventionmentioning
confidence: 99%
“…However, there are limited studies addressing its use in hospitalized subjects. 1,[6][7][8] Mayer and colleagues 9 reported 5 cases of agitated delirium in smokers hospitalized for brain injury. The delirium developed 2-10 days after smoking cessation, and either completely resolved or substantially improved following NRT.…”
Section: Discussionmentioning
confidence: 99%
“…Reid, Pipe, Higginson, Johnson, D'Angelo, Cooke, et al, 2003 To explore stepped-care interventions as a way reduce the cost of effective intervention for smokers which are often considered to be intensive and expensive A stepped-care approach to smoking cessation after hospitalization increased the short-but not the long-term smoking abstinence of patients.…”
Section: Case Methods Processmentioning
confidence: 99%
“…Connections have been found between patients' confidence in their ability to quit (self-efficacy) and successful outcomes (Reid, Pipe, Higginson, Johnson, D'Angelo, & Cooke et al, 2003). According to the literature, there are numerous factors and characteristics which have been associated with behavioural change and better "long-term abstinence following clinician-assisted smoking cessation including high education level, low nicotine dependence, low perceived stress, high proximal self-efficacy, greater social support, and abstinence during the first 1 to 2 weeks of treatment" (D'Angelo, Reid, Brown, & Pipe, 2001).…”
Section: Drivers: Patients' Motivation To Change the Current Situationmentioning
confidence: 99%